2001
DOI: 10.1063/1.1379989
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of gas-phase atomic hydrogen by Si(100): Effect of surface atomic structures

Abstract: The atomic-scale surface structural evolution of Si(100) exposed to gas-phase thermal hydrogen atoms, H(g), has been investigated by scanning tunneling microscopy and temperature-programed desorption mass spectrometry. For the substrate temperature (Ts) between 420 and 530 K, dihydride species in 3×1:H domains were selectively etched upon extensive exposures to H(g). As a result, etch pits grew laterally along Si surface dimer rows. The presence of these pits correlates with the absorption of H(g) into the bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…With each Si surface atom accommodating two H atoms, a fully Hsaturated surface is a (1 1) dihydride surface [9][10][11]. There also exists an intermediate (3 1) phase in which rows of monohydride dimers are interlaced with rows of dihydrides [9,[11][12][13][14]. Theory has shown that the (3 1) phase is more stable than separate (1 1) dihydride and (2 1) monohydride regions or other periodic patterns, but the free energy difference is relatively modest [15].…”
mentioning
confidence: 99%
“…With each Si surface atom accommodating two H atoms, a fully Hsaturated surface is a (1 1) dihydride surface [9][10][11]. There also exists an intermediate (3 1) phase in which rows of monohydride dimers are interlaced with rows of dihydrides [9,[11][12][13][14]. Theory has shown that the (3 1) phase is more stable than separate (1 1) dihydride and (2 1) monohydride regions or other periodic patterns, but the free energy difference is relatively modest [15].…”
mentioning
confidence: 99%
“…It has been well established that both Si(100) and Ge(100) surfaces reconstruct to make (2Í1) surfaces, on which each surface atom has only one dangling bond. Such dangling bonds are readily passivated by H(g) with a nearly unity sticking probability, leading to well-ordered monohydride-saturated surfaces, Si(100)-2 × 1:H [8][9][10][11][12] and Ge(100)-2 × 1:H [16][17][18][19][27][28]. Schematic views of the unit cell of a diamond crystal lattice and the (100)-2 × 1:H surface are drawn in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The relative importance of theses reactions is determined mostly by the substrate temperature. While the surface etching of Si(100) by H(g) is slow and anistropic at moderately elevated temperatures, it becomes faster and rather isotropic at room temperature [8,9]. At even lower temperatures, subsurface Si(100) hydrogenation/amorphization is a dominant reaction channel [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Interfacial defect states 2-10 and surface roughening [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] are the cause of many problems in gate oxide processing. 1 Interfacial defect states 2-10 and surface roughening [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] are the cause of many problems in gate oxide processing.…”
Section: Introductionmentioning
confidence: 99%